Introducing scrum process optimization - Ounsrimuang, Pimolrat; Nootyaskool, Supakit (My University, 2017)
Scrum is a well-known methodology in software development describing as organization in a developer team. A scrum team is a small size with expert members, rich communication, sharing knowledge, self-organization, and self-planning. Scrum process in this version developed by an attempt to create a self-organization team, which an action-reward function integrated in the proposed algorithm. This paper proposed a scrum process creating an optimization algorithm in the class of evolutionary computation. The proposed algorithm experimented on 30 numerical functions by the benchmark coding from the CEC2017 competition problems. The experiment results indicate that uses action-reward function to organize operation planning can help the proposed algorithm finding the best result.
Keywords: Optimization Algorithm; Reinforcement Learning; Scrum Process